Adaptation of Clinical Evaluation of Language Functions - 4th Edition to Brazilian Portuguese - Bento-Gaz,Ana Carolina Paiva (2014)
PURPOSES: To translate and adapt the Clinical Evaluation of Language Functions - 4th Edition (CELF-4) to Brazilian Portuguese. METHOD: One hundred and sixty normal language development school children between the ages of seven and ten, half from public schools and the other half from private schools, both located on the east side of São Paulo. RESULTS: CELF-4's translation and adjustment to Brazilian Portuguese language showed equivalence between the original and translated versions, which demonstrates that there were no significant changes in the test's form and content. Cronbach's α test was used in order to verify CELF-4's subtests internal consistency, in other words, if every subtest measures consistently the evaluated constructors. In this analysis, we observed that by excluding right or wrong items, and problematic items from the pool (those different from the rest of the group), all analyzed subtest presented satisfactory internal consistency, except for the Word Association Task for eight years old. CONCLUSION: Most subtests, as well as the Pragmatic Profile and the Observational Evaluation Scale, were simply translated, dismissing significant adaptations. The alterations performed were due to morphosyntactic and phonological differences between both languages. CELF-4's translated and adapted version to Brazilian Portuguese was able to characterize the language performance in the studied population.